Genetics and Genomics of Cotton Leaf Curl Disease, Its Viral Causal Agents and Whitefly Vector: A Way Forward to Sustain Cotton Fiber Security - Rahman, Mehboob-ur-; Khan, Ali Q.; Rahmat, Zainab; Iqbal, Muhammad A.; Zafar, Yusuf (Frontiers in Plant Science, 2017)
Cotton leaf curl disease (CLCuD) after its first epidemic in 1912 in Nigeria, has spread to different cotton growing countries including USA, Pakistan, India and China. The disease is of viral origin—transmitted by the whitefly Bemisia tabaci, which is difficult to control because of the prevalence of multiple virulent viral strains or related species. The problem is further complicated as the CLCuD causing virus complex has a higher recombination rate. The availability of alternate host crops like tomato, okra etc., and practicing mixed type farming systems have further exaggerated the situation by adding synergy to the evolution of new viral strains and vectors. Efforts to control this disease using host plant resistance remained successful using two gene based-resistance that was broken by the evolution of new resistance breaking strain called Burewala virus. Development of transgenic cotton using both pathogen and nonpathogenic derived approaches are in progress. In future, screening for new forms of host resistance, use of DNA markers for the rapid incorporation of resistance into adapted cultivars overlaid with transgenics and using genome editing by CRISPR/Cas system would be instrumental in adding multiple layers of defense to control the disease—thus fiber production will be sustained.